Corrosion resistance of Al–Cr-slag containing chromium–corundum refractories to slags with different basicity. Issue 11 (1st August 2018) - Wang, Xianghui; Zhao, Pengda; Chen, Jianwei; Zhao, Huizhong; He, Kai
Abstract: Al–Cr slag is the solid waste generated by the smelting of Cr metal. It presents a range of environmental hazards. This study addressed the corrosion resistance of Al–Cr slag containing chromium–corundum refractories to slags with different basicity. Herein, we provide suggestions for the use of Cr–corundum of different basicity in kilns. Al–Cr slag, brown fused Al2 O3, and chrome green were used as the raw materials, with pure calcium aluminate cement being used as a binder. The brick samples, prepared using different blends of chrome green and corundum, were fired at 1600 °C, and subsequently subjected to a slag corrosion test. After corrosion by slag of different basicity, the phase composition and microstructure of the sample were analyzed by X-ray diffraction, energy dispersive spectrometer and scanning electron microscopy. There were two major findings. First, Cr–corundum brick made from Al–Cr slag has a better slag corrosion resistance than that made from Cr2 O3 and brown fused Al2 O3 . Second, Cr–corundum brick made from Al–Cr slag has superior corrosion resistance to slag with a CaO:SiO2 ratio of 2:1.